Answer:
distance = 13
Step-by-step explanation:
The distance between two points (x1, y1) and (x2, y2) can be calculated as
![d=√((x_2-x_1)^2+(y_2-y_1)^2)](https://img.qammunity.org/2023/formulas/mathematics/college/ryn3fzehb0ozllfgi4eom8sc1fxhgg6wgd.png)
Replacing (x1, y1) = (8, 6) and (x2, y2) = (3, -6), we get that the distance between these points is
![\begin{gathered} d=√((3-8)^2+(-6-6)^2) \\ \\ d=√((-5)^2+(-12)^2) \\ \\ d=√(25+144) \\ \\ d=√(169) \\ \\ d=13 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7vifjvw4ci5bunxayfkwjpox17paxmfsq5.png)
Therefore, the distance between the points is 13.